Utilization of the Cepheid Xpert® CT/NG Sample Adequacy Control to Determine the Influence of the Urethral Swab on Cellular Content in Post-Swab versus Pre-Swab Urine - Jordan, Stephen J. (Sex Transm Dis, 2017)
Chlamydia trachomatis/Neisseria gonorrhoeae assay performance in males is typically determined using post-swab urine, though pre-swab urine is used in practice. We collected swabs and urine from men and used the Cepheid Xpert® CT/NG sample adequacy control to determine the effect of swab collection on urine cellular content. No difference was observed.